Estimation of genetic parameters for functional longevity in the South African Holstein cattle using a piecewise Weibull proportional hazards models. - (:unkn) unknown (My University, 2017)
Non-genetic factors influencing functional longevity and the heritability of thetrait were estimated in South African Holsteins using a piecewise Weibull proportional hazards model. Data consisted of records of 161,222 of daughters of 2,051 sires calving between 1995 and 2013. The reference model included fixed time-independent age at first calving and time-dependent interactions involving lactation number, region, season and age of calving, within-herd class of milk production, fat and protein content, class of annual variation in herd size and the random herd–year effect. Random sire and maternal grandsire effects were added to themodel to estimate genetic parameters. The within-lactation Weibull baseline hazards were assumed to change at 0, 270, 380 days and at drying date. Within-herd milk production class had the largest contribution to the relative risk of culling. Relative culling risk increased with lower protein and fat per cent production classes and late age at first calving. Cows in large shrinking herds also had high relative risk of culling. The estimate of the sire genetic variance was 0.0472 + or - 0.0017 giving a theoretical heritability estimate of 0.11 in the completeabsence of censoring. Genetic trends indicated an overall decrease in functional longevity of 0.014 standard deviation from 1995 to 2007. There are opportunities for including the trait in the breeding objective for South African Holstein cattle.
Keywords: African Research